Pendekatan-Pendekatan Konseling Keluarga - Hidayani Syam; Rifla Fasmawati; Sonia Sonia (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The family is the smallest social unit in society that plays an important role in individual development. Harmonius relationships within the family are the main foundation for creating individuals who are physically, emotionally, and psychologically healthy. Family Psychodynamics is an approach to family counseling that is rooted in psychoanalytic theory. This approach focuses on unconscious emotional patterns in relationships between family members, as well as the influence of childhood experiences on current family dynamics. Behavioral Social Family Counseling is an approach to family counseling that combines psychodynamic principles with social behavioral theory. This approach focuses on how social interactions and behaviors observed within the family affect the dynamics of relationships between family members.The Structural Family Approach is a counseling model that emphasizes family structure, including roles, hierarchies, and patterns of relationships between family members. This approach was developed by Salvador Minuchin, who believed that families have a structure that influences interactions between family members.